Agricultural damage following the recent expansion of wild boar ( Sus scrofa )—farmer perceptions and preconditions ... - Miettinen, Elmo; Pellikka, Jani; Kunnasranta, Mervi; Huitu, Otso (Taylor & Francis, 2024)
The wild boar ( Sus scrofa ) population has recently increased in Fennoscandia, leading to increasing interactions with humans, e.g. in the form of hunting opportunities or property damages. These experiences may shape the attitudes towards wild boars and affect their population management. We studied attitudes among 165 farmers towards wild boar by means of survey data. We also made preliminary estimates of wild boar damage costs in Finland. Our analysis revealed three attitude groups among farmers, emphasizing various perspectives: “hunting resource”, “pest-of-concern”, and “ambivalent”. The benefits, costs, feelings, and perceived wild boar population development partly explained the division. The direct annual damage costs in southeast Finland were broadly estimated to be circa 990,000€ and mitigation costs circa 350,000€. Reconciling differing opinions and goals into a widely accepted management strategy is a key precondition for sustainable coexistence. While the level of economic loss is so far not ...